2015
DOI: 10.4172/2155-6156.1000533
|View full text |Cite
|
Sign up to set email alerts
|

Type 2 Diabetes Mellitus- Disease, Diagnosis and Treatment

Abstract: Type 2 diabetes mellitus (T2DM) is a fast-growing disease and a leading global public health concern. Multiple complications are associated with T2DM. Patient education with lifestyle modifications and pharmacotherapy are main methods for treatment of patients afflicted with T2DM. Lifestyle interventions are effective strategies but usually persist for a short term whereas T2DM patients with long-term treatment still present challenges in many cases. In this review, we have briefly summarized recent progress f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Chronic hyperglycemia is associated with long-term damage, dysfunction, and failure of different organs, such as the eyes, kidneys, nerves, DOI: 10.30994/sjik.v9i2.255 ISSN: 2252-3847 (print); 2614-350X (online) Vol.9 No.2 November 2020 Page.629-634 heart, and blood vessels which results in increased levels of morbidity and mortality. (Zhao, Xu, Wu, & Yi, 2015). The condition of hyperglycemia in type 2 diabetes mellitus occurs because of a high concentration of glucose in the blood.…”
Section: Discussionmentioning
confidence: 99%
“…Chronic hyperglycemia is associated with long-term damage, dysfunction, and failure of different organs, such as the eyes, kidneys, nerves, DOI: 10.30994/sjik.v9i2.255 ISSN: 2252-3847 (print); 2614-350X (online) Vol.9 No.2 November 2020 Page.629-634 heart, and blood vessels which results in increased levels of morbidity and mortality. (Zhao, Xu, Wu, & Yi, 2015). The condition of hyperglycemia in type 2 diabetes mellitus occurs because of a high concentration of glucose in the blood.…”
Section: Discussionmentioning
confidence: 99%
“…Base on previous study the number of people with diabetes continues to increase as reported by the International Diabetes Federation (IDF) where in 2017 there were 425 million people suffering from diabetes and it is estimated that 629 million people by 2045 (Galicia-Garcia et al, 2020). Among the types of diabetes that have been described, diabetes mellitus type 2 has the highest prevalence which represents >90% of all diabetics (Guangcui Xu, 2015;Javeed & Matveyenko, 2018;Laakso, 2019). The increasing incidence of this disease is expected to continue and in the United States alone it is estimated that it will affect one in three people by 2050 (Khan et al, 2020;Ligita et al, 2019;Lu et al, 2019).…”
Section: Introductionmentioning
confidence: 99%